Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.tem.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of hormone-dependent cancers: a bird's eye view

Abstract: Hormone-dependent cancers present a significant public health challenge, as they are among the most common cancers in the world. One factor associated with cancer development and progression is metabolic reprogramming. By understanding these alterations, we can identify potential markers and novel biochemical therapeutic targets. Metabolic profiling is an advanced technology that allows investigators to assess low molecular weight compounds that reflect physiological alterations. Current research in metabolomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 90 publications
0
33
0
Order By: Relevance
“…AI are drugs commonly used to treat BC that work through a different mechanism to that of Tam, by inhibiting the production of estrogen from androgen [2]. Recent literature has highlighted the role of OS, oxygenated cholesterol derivatives, in BC progression [3][4][5][6] and resistance to Tam [7][8][9][10][11][12]. The impact of AI on OS metabolism is currently unknown.…”
mentioning
confidence: 99%
“…AI are drugs commonly used to treat BC that work through a different mechanism to that of Tam, by inhibiting the production of estrogen from androgen [2]. Recent literature has highlighted the role of OS, oxygenated cholesterol derivatives, in BC progression [3][4][5][6] and resistance to Tam [7][8][9][10][11][12]. The impact of AI on OS metabolism is currently unknown.…”
mentioning
confidence: 99%
“…Recent reviews attempting to synthesize such post-diagnosis prostate cancer metabolomic data reveal diverse patient populations, study methods, laboratory platforms, and biological samples with mixed outcomes [84,85]. One focused on individual metabolite signals and found little replication across the clinical studies [85], while the other evaluated metabolite classes and metabolic pathways and noted patterns consistent with lipid and energy pathway dysregulation [84], similar to the pre-diagnostic prospective data described below. This apparent concordance at the pathway level across different study approaches is encouraging regarding our understanding of prostate cancer, and suggests it may be a more valuable approach for synthesizing data across studies than examining only individual metabolite signals.…”
Section: Metabolomic Profiling Of Vitamin Status and Prostate Cancer mentioning
confidence: 99%
“…A wide variety of biological samples have been profiled for prostate cancer cases with diverse clinical and histopathological characteristics (e.g., stage and Gleason), including tissue from biopsies, radical prostatectomies, and distant metastases. Serum or plasma from both fasting and non-fasting participants, as well as urine can be assayed [84,85]. Metabolomic profiling of such different samples and populations might be expected to yield diverse and inconsistent findings that will require synthesis and a more comprehensive concept of disease development and progression.…”
Section: Metabolomic Profiling Of Vitamin Status and Prostate Cancer mentioning
confidence: 99%
“…In addition to the Warburg effect, glioblastoma tumor cells also utilize the tricarboxylic acid cycle/oxidative phosphorylation in a different capacity relative to normal tissue. In recent years, metabolomics‐based approaches have been recognized as an emerging tool to discover novel biomarkers for cancer including early detection, diagnosis, prognosis, and the assessment of drug efficacy …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metabolomics-based approaches have been recognized as an emerging tool to discover novel biomarkers for cancer including early detection, diagnosis, prognosis, and the assessment of drug efficacy. [2][3][4][5][6][7][8][9][10][11] Metabolomics profiling in glioblastoma has only recently begun to emerge. [12][13][14][15][16][17][18][19][20][21][22][23] For example, in glioblastoma cell lines, Palanichamy et al identified a four-metabolite signature that played an important role in promoting and maintaining the growth of glioblastoma.…”
Section: Introductionmentioning
confidence: 99%